Tracing the coevolution between Triatoma infestans and its fungal pathogen Beauveria bassiana - Mannino, Maria Constanza (2018)
The chemical control of Triatoma infestans, the major Chagas disease vector in southern South America, has been threatened in the last years by the emergence of pyrethroid-resistant bug populations. As an alternative approach, the efficacy of the entomopathogenic fungus Beauveria bassiana to control T. infestans populations (regardless their pyrethroid susceptibility) has been demonstrated. Growing research efforts on the interaction between T. infestans and B. bassiana by molecular, ecological, biochemical and behavioral traits has allowed framing such interaction as an evolutionary arms race. This review will focus on the relationships established in this particular host-pathogen system, compiling available data on the relevance of fungal pathogenesis, insect behavior, population dynamics and human intervention to favor fungal dissemination in bug populations. The current snapshot shows the fungus ahead in the evolutionary arms race and predicts a promissory landscape for the biological control of Chagas disease vectors.